The Effect of Governance Mechanisms and Ownership Structure on the Financial Performance of Banking Companies on the Indonesian Stock Exchange - Irma Sukamdi; Tubagus Ismail; Prisilia Damayanti (DINASTI RESEARCH, 2026)
This study aims to analyze the effect of Good Corporate Governance, which consists of the board of directors, independent commissioners, and audit committees, as well as the effect of ownership structure, which consists of managerial ownership and institutional ownership, on financial performance. The population used is all banking sector companies listed on the Indonesia Stock Exchange from 2020 to 2024. The sampling technique used was purposive sampling with the criteria of companies that published complete financial reports, experienced profits, and had complete data in accordance with the research variables during the period from 2020 to 2024, as well as companies that had complete data in accordance with the research variables. The sample obtained was 110 observations. The data source used was secondary data, with the data collection method using documentation. The data analysis technique used was panel data linear regression using e-views version 12. The results showed that the board of directors had a significant effect on financial performance, independent commissioners had no significant effect on financial performance, the audit committee had a significant effect on financial performance, managerial ownership had a significant effect on financial performance, and institutional ownership had a significant effect on financial performance.